2018
DOI: 10.1371/journal.pbio.2004825
|View full text |Cite
|
Sign up to set email alerts
|

Bonobo and chimpanzee gestures overlap extensively in meaning

Abstract: Cross-species comparison of great ape gesturing has so far been limited to the physical form of gestures in the repertoire, without questioning whether gestures share the same meanings. Researchers have recently catalogued the meanings of chimpanzee gestures, but little is known about the gesture meanings of our other closest living relative, the bonobo. The bonobo gestural repertoire overlaps by approximately 90% with that of the chimpanzee, but such overlap might not extend to meanings. Here, we first determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
92
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 77 publications
(93 citation statements)
references
References 40 publications
0
92
0
Order By: Relevance
“…For example: gesturing is adjusted to the visual orientation of the target recipient (e.g., Cartmill and Byrne 2007;Leavens et al 2005b;Liebal et al 2004); signallers persist in, and sometimes elaborate, their gesturing until their goal is achieved (e.g. Cartmill and Byrne 2007;Leavens et al 2005b;Hobaiter and Byrne., 2011b;Roberts et al 2014b); and gestures are characterized by a flexible relationship between signal and outcome (means-ends dissociation), implying individual signallers are able to use different signals/gestures to achieve the same outcome/goal, or a single gesture for several outcomes (Graham et al, 2018;Liebal et al 2006;Pika et al 2003;Tomasello et al 1994). (Bard et al 2014a;Liebal et al 2013;Pika and Fröhlich 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For example: gesturing is adjusted to the visual orientation of the target recipient (e.g., Cartmill and Byrne 2007;Leavens et al 2005b;Liebal et al 2004); signallers persist in, and sometimes elaborate, their gesturing until their goal is achieved (e.g. Cartmill and Byrne 2007;Leavens et al 2005b;Hobaiter and Byrne., 2011b;Roberts et al 2014b); and gestures are characterized by a flexible relationship between signal and outcome (means-ends dissociation), implying individual signallers are able to use different signals/gestures to achieve the same outcome/goal, or a single gesture for several outcomes (Graham et al, 2018;Liebal et al 2006;Pika et al 2003;Tomasello et al 1994). (Bard et al 2014a;Liebal et al 2013;Pika and Fröhlich 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Gestures were employed to achieve eight distinct goals, including six positive requests (Acquire object; Climb on me; Climb on you; Climb over; Play change; Play continue) and two negations (Move away; Stop behavior). As found in chimpanzees and bonobos (Graham et al 2018;Hobaiter and Byrne 2014), gestures were employed flexibly toward multiple goals, but the majority of gesture types were used to achieve at least one play-related goal; thus, flexibility decreased (to an average of two goals per gesture type) when play data were removed. These findings suggest that orang-utans also show means-ends dissociation in their gesturing, with individual gesture types used to achieve several distinct goals and several gestures employed to express an individual goal.…”
Section: Discussionmentioning
confidence: 93%
“…We did not have sufficient cases of successful gesture use per individual to explore whether specific goals were associated with each gesture type. However, as research has shown that individual signaler identity did not impact signal meaning (Graham et al 2018; Hobaiter and Byrne 2014), we present a preliminary investigation here in which gesture use was combined across signalers. After a gesture was employed, the reaction that caused the signaler to stop signaling was deemed to be the apparently satisfactory outcome, or goal, of the gesture.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Findings regarding gestural communication in great apes, including inter-species comparisons, evoke a similar general interpretation. [94][95][96] Altogether, the burgeoning strand of great ape vocal research [28,91,97] shows that traditional ideas about what great apes can and (mostly) cannot do are outdated, too crude or unsubstantiated. The precursor system for (spoken) language evolution will be best understood when zooming out our theoretical and empirical lenses to include the vocal (and gestural) behavior of all great ape genera, including its neural and molecular substrates.…”
Section: Living Links Between Great Ape Vocal Skills and Human Verbalmentioning
confidence: 99%